2013
DOI: 10.5056/jnm.2013.19.2.233
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Eradication on Functional Dyspepsia

Abstract: Background/AimsThis study evaluated the effect of Helicobacter pylori eradication on functional dyspepsia (FD), and the relationship between the changes of histological gastritis and FD symptom responses.MethodsA total of 213 FD patients diagnosed by Rome III criteria were consecutively enrolled. H. pylori tests and gastritis grade by the Sydney system were performed before and 1 year after the proton pump based-eradication therapy for 7 days. Serum levels of pepsinogen, and genetic polymorphisms IL-6, IL-8 an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
50
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 64 publications
(53 citation statements)
references
References 42 publications
2
50
0
1
Order By: Relevance
“…The genetic factors associated with FD include the genetic variant C825T in GNβ3 (Dai et al, 2014), the COX-1 gene polymorphism , polymorphism in codon 158 of the Catechol-Omethyltransferase (COMT) gene . The other potential risk factors of FD are gender, age, smoking, psychological disturbances and Helicobacter pylori (H. pylori) infection (Li et al, 2002;Shaib and El-Serag, 2004;Mahadeva and Goh, 2011;Ford, 2012;Filipovic et al, 2013;Kim et al, 2013). Furthermore, those with H. pylori infection will get chance to develop gastric cancer between three to six times more than uninfected persons (Forman et al, 1991;Nomura et al, 1991;Parsonnet et al, 1991).…”
Section: Introductionmentioning
confidence: 99%
“…The genetic factors associated with FD include the genetic variant C825T in GNβ3 (Dai et al, 2014), the COX-1 gene polymorphism , polymorphism in codon 158 of the Catechol-Omethyltransferase (COMT) gene . The other potential risk factors of FD are gender, age, smoking, psychological disturbances and Helicobacter pylori (H. pylori) infection (Li et al, 2002;Shaib and El-Serag, 2004;Mahadeva and Goh, 2011;Ford, 2012;Filipovic et al, 2013;Kim et al, 2013). Furthermore, those with H. pylori infection will get chance to develop gastric cancer between three to six times more than uninfected persons (Forman et al, 1991;Nomura et al, 1991;Parsonnet et al, 1991).…”
Section: Introductionmentioning
confidence: 99%
“…Previous reports revealed that responders at 3 months and H. pylori eradicated status were associated with improvement of dyspeptic symptoms at 1 year, regardless of the overplayed IBS. 43 Gastric mucosal inflammation induced by H. pylori infection was a crucial role in symptom generation, and the control of inflammation resulted in symptom improvement. Therefore, the Kyoto Global Consensus report insisted that H. pylori-associated dyspepsia was not as a FD, but a kind of infectious disease.…”
Section: Discussionmentioning
confidence: 99%
“…The patients' demographic and clinical data, including age, sex, history of previous H. pylori eradication treatment, and endoscopic findings, were gathered. H. pylori infection was defined by a positive rapid urease test result (CLO test; Delta West, Bentley, Australia) during a gastric mucosal biopsy procedure performed on the lesser curvature of the midantrum or midbody and/or by a positive result showing histological evidence of H. pylori with modified Giemsa staining in the gastric mucosal biopsy specimen from the lesser curvature and greater curvature of the midantrum and midbody (18).…”
Section: Methodsmentioning
confidence: 99%
“…To detect H. pylori 23S rRNA mutations related to clarithromycin resistance, H. pylori genomic DNA was extracted from the isolates (18,21). Specimens were homogenized in proteinase K solution (20 mmol/liter TrisHCl [pH 8.0], 10 mmol/liter EDTA, 0.5% sodium dodecyl sulfate, and 10 mg/ml proteinase K) by using a sterile micropestle and incubated for 3 h. DNA was isolated by phenol-chloroform extraction and ethanol precipitation.…”
Section: Methodsmentioning
confidence: 99%